2007
DOI: 10.1007/s11626-007-9032-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro host range of the Hz-1 nonoccluded virus in insect cell lines

Abstract: A total of 13 insect cell lines spanning 4 orders (Lepidoptera, Coleoptera, Diptera, and Homoptera) were tested for their ability to replicate the nonoccluded virus Hz-1. Only the Lepidopteran cell lines supported replication of the virus with TN-CL1 and BCIRL-HZ-AM1 producing the highest titers of 2.4 x 10(8) tissue culture infective dose (TCID)50/ml and 2.0 x 10(8) TCID50/ml, respectively. A codling moth cell line (CP-169) was the only Lepidopteran cell line that did not replicate the virus and transfection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The permissive cell line BCIRL-HzAM1 produced a titer of 3.3ϫ10 5 TCID 50 /ml following challenge with HzSNPV. The Hz-1 virus which has a very wide in vitro host range (McIntosh et al, 2007) produced a titer of 3.7ϫ10 6 TCID 50 /ml in BCIRL-DP-AM/JG as contrasted with a 2 log cycle higher titer of 4.3ϫ10 8 TCID 50 /ml in the permissive cell line BCIRLHzAM1.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The permissive cell line BCIRL-HzAM1 produced a titer of 3.3ϫ10 5 TCID 50 /ml following challenge with HzSNPV. The Hz-1 virus which has a very wide in vitro host range (McIntosh et al, 2007) produced a titer of 3.7ϫ10 6 TCID 50 /ml in BCIRL-DP-AM/JG as contrasted with a 2 log cycle higher titer of 4.3ϫ10 8 TCID 50 /ml in the permissive cell line BCIRLHzAM1.…”
Section: Resultsmentioning
confidence: 97%
“…The BCIRL-DP-AM/JG was susceptible to 4 baculoviruses used in this study but was refractile to a 5th, the HzSNPV. The monarch butterfly cell line was also susceptible to the Hz-1 non-occluded virus which does not produce OB but results in the degeneration of inoculated cells (McIntosh et al, 2007). AcMNPV-HPP replicated to a titer of 1.9ϫ10 7 TCID 50 /ml in BCIRL-DP-AM/JG as compared with 3.2ϫ10 7 TCID 50 /ml in the permissive cell line BCIRL-HsAM1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(47,48). The HzNV-1 virus has a relatively broad host range and has been reported to productively and latently infect many insect cell lines (4,14,24,31,34,35,40). Previously, we found that more than 100 transcripts are produced during productive HzNV-1 virus infection (6); during this phase of infection, a gene located on the HzNV-1 HindIII-I fragment (hhi1) was found to generate an abundant 6.2-kb transcript within 0.5 h postinfection (hpi) (50,51).…”
mentioning
confidence: 99%
“…This virus has been reported to infect many insect cell lines including Trichoplusia ni (TN-368), Spodoptera frugiperda (IPLB-SF-21), H. zea (IPLB-1075), Mamestra brassicae, and Porthetria dispar (IPLB-65Z) (1,8,22,25) and to establish latent infections in most of these insect cell lines, which are permissive to this virus. HzNV-1 virus is an enveloped, rodshaped, nonoccluded virus with a circular double-stranded DNA genome of 228 kb, which is encased in a 414 Ϯ 30 nm nucleocapsid (1,3,4,11).…”
mentioning
confidence: 99%